Comparison of exercise in a green outdoor environment versus indoor activities among cardiac survivors - Amat, Nur Syakira Amira; Abdul Shukor, Shureen Faris (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Heart disease is the number one killer in Malaysia and alarmingly, the numbers of the patients are increasing throughout the year. Currently, the rehabilitation therapy for the cardiac patients are mostly using the equipment found in the rehabilitation unit, rather than utilising the green outdoor environments (GOEs) which can be found within the hospitals’ compounds. There is still a lack of study using GOE for cardiac patients’ rehabilitation therapy. The main purpose of this study is to identify the effectiveness of using indoor and outdoor as the settings for the rehabilitation therapy for the cardiac patients. This study was carried out at The Rehabilitation Department of Serdang General Hospital in Malaysia where rehabilitation treatments especially for cardiac patients were carried out twice weekly. The patients suffered the Coronary Artery Disease were selected for this study. The patients were exposed to both indoor and outdoor settings during the treatments. The patients’ heart rate and blood pressure will be the indicators for the effectiveness of the treatment received. A survey using questionnaires will also applied in order to identify the preferences of the patients on the types of elements that they would like to have within the indoor or the green outdoor environment. The results from this on-going study may help to identify the preferences for the setting of the patients under-going the rehabilitation therapy at hospitals and also, providing the recommendations for the design of green outdoor environment as a rehabilitation area.